Tradisi Budaya Madura di Desa Candijati, Kec. Arjasa, Kabupaten Jember - Bagas Eko Firmansyah; M. Dwi Bintang Ramadhan; Audy Yourdiansyah Firdaus; Hasan Suaedi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study examines the preservation of Madurese cultural traditions in Candijati Village, Arjasa District, Jember Regency. The primary focus is on traditions such as tanèyan lanjèng, rokat tasek, sapi sonok, and Madurese ludruk. These traditions face challenges in the era of modernization, including lifestyle changes and the influence of global culture. The research employs a qualitative method with in-depth interviews and direct observations as data collection techniques. The findings reveal that the people of Candijati Village hold diverse views on Madurese cultural traditions. Most still respect and practice these traditions as a form of cultural identity, while others have begun to abandon them, considering them less relevant in the modern era. The role of the community, including traditional leaders and local artists, is pivotal in maintaining these traditions. Preservation strategies that involve educating younger generations and gaining support from local governments are considered crucial to ensure the sustainability of Madurese cultural traditions. This study contributes to understanding the dynamics of local culture amid the challenges of modernization and offers relevant approaches for cultural preservation aligned with contemporary contexts. It is hoped that this article will serve as an important reference for preserving local culture as part of the nation's rich identity.